In India, the Privatization of Medical Education Has Created a Health-Care Conundrum (International Journal of Innovative Research in Engineering & Management, 2023)
Medical education privatization can  increase its breadth and usability by producing a set of  osteopathic medical professionals for Indians, so how can  it be a replacement to building capacity with the expertise  and skill mix, particularly when services are needed? Involving human lives require urgent rethinking? The goal  of this study is to look at the problems surrounding the  privatization of India's medical education system.  Materials and Procedures: Since the past 20 years, a  systematic evaluation of major indexed journals of key  medical search engines, such as Pub med, Here on primary  search words "Corporatization of Health Schooling," we  searched Lancet, Microbe Online, and Google Scholar in  all forms, including u t. India ranks 67th out from 133  underdeveloped countries in a WHO survey, with just a  pediatrician proportion of 1:1700, contrasted to a  nationwide average of 1.5:1000. That is to say, despite  over than fifty years of freedom, not a single doctor is  available for every 1000 people; a goal that is still a long  way off, according to the Bhore committee's  recommendation in 1946, which was later modified by the  Mudaliar committee in 1961 and the Bajaj committee in  1987.
Keywords: Allopath; Bio-Med; Health Care; Private Medical Education; Medical Education